Feasibility Study of UHPC Reinforced Masonry Structure - Chen, Yang; Wang, Shaojie (Journal of Theory and Practice of Engineering Science, 2024)
With the increase of service life of masonry structure and the damage of masonry structure caused by external environment, the structure will be difficult to meet the design requirements. It is necessary to repair and reinforce the existing structure or replace the original structure with a new type of composite structure. ultra-high performance concrete (UHPC) is a kind of high strength, high ductility, high durability material, which has the advantages of almost impermeability, almost no carbonization, and almost zero chloride ion penetration and sulfate penetration. UHPC has been widely used in the field of concrete structure reinforcement, whether the masonry structure can be better strengthened has become the research content of this paper. Basic mechanics of UHPC materials at home and abroad By systematically combing and summarizing the research progress of performance and reinforcement design, the feasibility of UHPC reinforced masonry structure is obtained.